Conceptual Framework for Risk Management in the Container Shipping Operations to Support Maritime Logistics in Indonesia - Fasih, Ahmad; Yuliawati, Evi (International Journal of Marine Engineering Innovation and Research, 2024)
Risk management is an important thing to do in every business activity and by business operator to ensure business continuity. The trend of increasing container shipping volumes in Indonesia shows the increasing need for a low-cost logistics distribution with large volumes. This condition will also be balanced by an increase in potential risks in container shipping operations. Previous research generally focuses on certain activities or locations, and there has not been much research on risk management in container shipping operations in a sequence activities of supply chain. The various risk management methods that exist today provide many options for implementation. This condition also provides an opportunity and is important to do further research in this area. This research is devoted to risk management of container shipping operations activities, and is intended to determine risk management research trends, existing risk management methods, potential or research gaps for further research as well as risk management framework concepts that can be proposed. The research was carried out using bibliometric analysis and systematic literature review of previous research, interpreting the results in the form of qualitative descriptions to answer existing problems. Research results show an increasing research trend for the last 5 years, with 18 method of risk management applied. This research provides a concept of how to assess container shipping operation risk management related to logistic supply chain.   The option of integrating 3 risk management approach methods, namely SCOR, CSORA and HOR, is proposed in this research, as a conceptual framework for risk management in container shipping operations to support maritime logistics in Indonesia, including propose location or object and aspects for further research, and 3 key success factors to implement the conceptual framework as a reference.